Breaking the Blockchain Trilemma: A Comprehensive Consensus Mechanism for Ensuring Security, Scalability, and Decentralization - Khandakar Md Shafin; Saha Reno (IET Software)
The ongoing challenge in the world of blockchain technology is finding a solution to the trilemma that involves balancing decentralization, security, and scalability. This paper introduces a pioneering blockchain architecture designed to transcend this trilemma, uniting advanced cryptographic methods, inventive security protocols, and dynamic decentralization mechanisms. Employing established techniques such as elliptic curve cryptography, Schnorr verifiable random function, and zero-knowledge proof (zk-SNARK), alongside groundbreaking methodologies for stake distribution, anomaly detection, and incentive alignment, our framework sets a new benchmark for secure, scalable, and decentralized blockchain ecosystems. The proposed system surpasses top-tier consensuses by attaining a throughput of 1700+ transactions per second, ensuring robust security against all well-known blockchain attacks without compromising scalability and demonstrating solid decentralization in benchmark analysis alongside 25 other blockchain systems, all achieved with an affordable hardware cost for validators and an average CPU usage of only 16.1%.